Optimization on Maltodextrin Concentration and Inlet Spray Drying Temperature in Producing Edamame (Glycine max L. Merr.) Milk Powder: Nutritional and Microbiological Profile. Issue 1 (June 2020) - Ali, D Y; Pranowo, D; Sunarharum, W B; Prananto, Y P; Tansil, C Z L
Abstract: Edamame powdered milk products have not produced on an industrial scale until the present. It is an excellent opportunity to develop nutrient-rich edamame to become a product with a high global market demand. The production of edamame milk powder has essential factors that contribute to sensory attributes, there is a concentration of maltodextrin as a filler and also encapsulating agent and inlet temperature of spray drying inlet for producing milk powder. The research aims to determine the optimal concentration of maltodextrin and inlet spray drying temperature to produce edamame milk powder based on the response of sensory analysis. Based on the results of the study, the concentration of maltodextrin 129.91 g/L (12.99%) and the spray dryer temperature 131°C were the optimal factor points of the sensory attribute responses analyzed using a nine-scale Hedonic Scale Scoring. Color with response 8.5, aroma 8.25, taste 7.8, and texture 8.35. The optimal product has a moisture content of 2.31 ± 0.04%, total dissolved solids of 19.89 ± 0.02% °Brix, the solubility of 95.23 ± 0.38%, and yield of 24.25%.